From anti-aging drugs to cancer therapy: is there a potential for sirtuin activators in gliomas? - Opitz, Christiane; Turcan, S̨evin (Neuro-Oncology, 2021)
See the article by Miller et al. pp. 53-62.Mutations in isocitrate dehydrogenase 1 (IDH1) and, to a lesser extent, IDH2 are hallmarks of lower-grade gliomas. IDH enzymes normally catalyze the decarboxylation of isocitrate to alpha-ketoglutarate (α-KG), but the hotspot recurrent mutations in IDH confer a neomorphic enzymatic activity that leads to overproduction of 2-hydroxyglutarate (2-HG) via NADPH-dependent reduction of α-KG.1 A distinctive outcome of 2-HG accumulation is the genome-wide DNA hypermethylation observed in IDH mutant tumors.2 In addition to its role in promoting epigenetic alterations, mutant IDH1 affects multiple metabolic pathways such as the citric acid cycle, glucose, glutamine, and lipid metabolism.3 To gain insights into these metabolic alterations and to determine whether they create metabolic vulnerabilities in IDH mutant tumors, further investigations are warranted. In this issue of Neuro-Oncology, Miller et al shed light on a metabolic Achilles’ heel in IDH mutant gliomas and demonstrate that sirtuin 1 (SIRT1) activation leads to augmented NAD+ depletion, reduced growth, and increased cytotoxicity when combined with nicotinamide phosphoribosyltransferase inhibitors (NAMPTi) in IDH mutant cells (Fig. 1).4
Advance access date 16 October 2020
Gesehen am 17.06.2021